Purification and characterization of a cyclomaltodextrin glucanotransferase from Paenibacillus campinasensis strain H69-3 - Alves-Prado, Heloiza Ferreira; Gomes, Eleni; da Silva, Roberto (Humana Press Inc, 2007)
A cyclomaltodextrin glucanotransferase (E.C. 2.4.1.19) from a newly isolated alkalophilic and moderately thermophilic Paenibacillus campinasensis strain H69-3 was purified as a homogeneous protein from culture supernatant. Cyclomaltodextrin glucanotransferase was produced during submerged fermentation at 45 degrees C and purified by gel filtration on Sephadex G50 ion exchange using a Q-Sepharose column and ion exchange using a Mono-Q column. The molecular weight of the purified enzyme was 70 kDa by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and the pI was 5.3. The optimum pH for enzyme activity was 6.5, and it was stable in the pH range 6.0-11.5. The optimum temperature was 65 degrees C at pH 6.5, and it was thermally stable up to 60 degrees C without substrate during 1 h in the presence of 10 mm CaCl2. The enzyme activity increased in the presence of Co2+, Ba2+, and Mn2+. Using maltodextrin as substrate, the K-m and K-cat were 1.65 mg/mL and 347.9 mu mol/mg.min, respectively.
Keywords: CGTase characterization; CGTase purification; cyclomaltodextrin glucanotransferase; thermostable CGTase